2014
DOI: 10.1002/ijc.28797
|View full text |Cite
|
Sign up to set email alerts
|

In vivo disposition of doxorubicin is affected by mouse Oatp1a/1b and human OATP1A/1B transporters

Abstract: Organic anion-transporting polypeptides (OATPs) are important drug uptake transporters, mediating distribution of substrates to several pharmacokinetically relevant organs. Doxorubicin is a widely used anti-cancer drug extensively studied for its interactions with various drug transporters, but not OATPs. Here, we investigated the role of OATP1A/1B proteins in the distribution of doxorubicin. In vitro, we observed ∼ 2-fold increased doxorubicin uptake in HEK293 cells overexpressing human OATP1A2, but not OATP1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 38 publications
4
34
0
Order By: Relevance
“…To the best of our knowledge, this is the first report using polarized MDCKII cells transfected stably by OATP1A2 and MDR1 cDNA constructs for drug transport. Collectively, our data indicate doxorubicin is a good substrate for OATP1A2, which is in agreement with a previous report demonstrating OATP1A2-mediated doxorubicin transport in HEK293 cells (Durmus et al, 2014).…”
Section: Oatps and Doxorubicin Dispositionsupporting
confidence: 93%
See 3 more Smart Citations
“…To the best of our knowledge, this is the first report using polarized MDCKII cells transfected stably by OATP1A2 and MDR1 cDNA constructs for drug transport. Collectively, our data indicate doxorubicin is a good substrate for OATP1A2, which is in agreement with a previous report demonstrating OATP1A2-mediated doxorubicin transport in HEK293 cells (Durmus et al, 2014).…”
Section: Oatps and Doxorubicin Dispositionsupporting
confidence: 93%
“…Our initial studies revealed doxorubicin to be an efficient substrate for human OATP1A2, but not OATP1B1 and OATP1B3, when assessed in detail using a recombinant vaccinia-based method in a HeLa cell system. However, for reasons that are not well-defined, OATP-mediated uptake of certain substrates, including drugs such as doxorubicin and docetaxel, has been noted by other groups to be variably discrepant in results among in vitro systems or when comparing in vitro to in vivo transport (Smith et al, 2005;de Graan et al, 2012;Durmus et al, 2014;Lee et al, 2015). Hence, absence of doxorubicin transport in HeLa cells does not preclude it to be transported in vitro by OATP1B transporters in another system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, transgenic humanized OATP1A/1B mouse models were generated with liverspecific expression of OATP1B1, OATP1B3, and OATP1A2 in an Oatp1a/1b knockout background. This model was utilized to show that paclitaxel, methotrexate, SN-38, docetaxel, and doxorubicin are transported by OATP1A/1B in vivo (19,20,57,58).…”
Section: Animal Models To Investigate the Role Of Oatps In The Disposmentioning
confidence: 99%